Diagnosing central lesions of the triangular fibrocartilage as traumatic or degenerative: a review of clinical accuracy - Löw, Steffen; Unglaub, Frank; Spies, Christian (The journal of hand surgery. European volume, 2017)
This study examined the reliability of surgeons’ estimations as to whether central lesions of the triangular fibrocartilage complex were traumatic or degenerative. A total of 50 consecutive central triangular fibrocartilage complex lesions were independently rated by ten experienced wrist surgeons viewing high-quality arthroscopy videos. The videos were reassessed after intervals of 3 months; at the second assessment surgeons were given the patient’s history, radiographs and both, each in a randomized order. Finally, the surgeons assessed the histories and radiographs without the videos. Kappa statistics revealed fair interrater agreement when the histories were added to the videos. The other four modalities demonstrated moderate agreement, with lower Kappa values for the assessment without videos. Intra-rater reliability showed fair agreement for three surgeons, moderate agreement for two surgeons and substantial agreement for five surgeons. It appears that classification of central triangular fibrocartilage complex lesions depends on the information provided upon viewing the triangular fibrocartilage complex at arthroscopy.